Prevalence of adherence to cardiovascular drugs in outpatients with coronary artery disease - Maria M. CRUZEIRO; Ronara S. GROIA-VELOSO; Bianca M. DIAS; Adriano M. REIS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objectives: To describe the prevalence of adherence to drug treatment and the association with sociodemographic, clinical and pharmacotherapeutic factors, in patients diagnosed with coronary artery disease, seen at a multiprofessional cardiology clinic in a public hospital in Belo Horizonte, Minas Gerais. Methods: This is a cross-sectional study conducted between April 2018 and February 2019 in a multiprofessional outpatient cardiology clinic at a teaching hospital. The dependent variable is adherence to treatment with cardiovascular drugs measured by self-report using the 7-day recall and the independent variables evaluated were the sociodemographic, clinical and pharmacotherapeutic variables. Descriptive analysis was performed using frequency distributions for categorical variables and measures of central tendency and dispersion for continuous variables. The association between treatment adherence and independent variables was performed using bivariate analysis using Pearson's chi-square test and the magnitude of the association was expressed by the odds ratio with a 95% confidence interval. Results: 148 patients with a median age of 62 years (IQR = 17.0), mostly male (104; 70.3%) and a median of four years of education (IQR = 4.0). The most prevalent cardiovascular diagnosis was ST-segment elevation acute myocardial infarction (58.8%), followed by non-ST-segment elevation acute myocardial infarction (26.4%) and arrhythmia (23.7%). The most frequent comorbidities were hypertension (72.3%) and diabetes (33.1%). Beta-blockers 98.1% (n = 130) and renin-angiotensin system agents 68.3% (n = 101) were the most commonly used cardiovascular drug classes. No statistically significant association was identified between adherence and sociodemographic, clinical and pharmacotherapeutic factors. Conclusion: The frequency of adherence to treatment measured by 7-days recall was high.